2023
DOI: 10.1002/advs.202206732
|View full text |Cite
|
Sign up to set email alerts
|

CircTmeff1 Promotes Muscle Atrophy by Interacting with TDP‐43 and Encoding A Novel TMEFF1‐339aa Protein

Abstract: Skeletal muscle atrophy is a common clinical feature of many acute and chronic conditions. Circular RNAs (circRNAs) are covalently closed RNA transcripts that are involved in various physiological and pathological processes, but their role in muscle atrophy remains unknown. Global circRNA expression profiling indicated that circRNAs are involved in the pathophysiological processes of muscle atrophy. circTmeff1 is identified as a potential circRNA candidate that influences muscle atrophy. It is further identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Skeletal muscle atrophy is a common clinical feature of many acute and chronic diseases. Chen et al (2023b) analyzed the expression profile of circRNA and showed that circRNA was involved in the pathophysiological process of muscle atrophy. CircTmeff1 was identified as a potential circRNA candidate affecting muscle atrophy.…”
Section: Circrna-encoded Proteins In Other Systemsmentioning
confidence: 99%
“…Skeletal muscle atrophy is a common clinical feature of many acute and chronic diseases. Chen et al (2023b) analyzed the expression profile of circRNA and showed that circRNA was involved in the pathophysiological process of muscle atrophy. CircTmeff1 was identified as a potential circRNA candidate affecting muscle atrophy.…”
Section: Circrna-encoded Proteins In Other Systemsmentioning
confidence: 99%